Elicitation of Andrographolide in the Suspension Cultures of Andrographis paniculata - Gandi, Suryakala; Rao, Kiranmayee; Chodisetti, Bhuvaneswari; Giri, Archana (Applied biochemistry and biotechnology, 2012)
Andrographis paniculata belonging to the family Acanthaceae produces a group of diterpene lactones, one of which is the pharmaceutically important—andrographolide. It is known to possess various important biological properties like anticancer, anti-HIV, anti-inflammatory, etc. This is the first report on the production of andrographolide in the cell suspension cultures of Andrographis paniculata by ‘elicitation’. Elicitation was attempted to enhance the andrographolide content in the suspension cultures of Andrographis paniculata and also to ascertain its stimulation under stress conditions or in response to pathogen attack. The maximum andrographolide production was found to be 1.53 mg/g dry cell weight (DCW) at the end of stationary phase during the growth curve. The biotic elicitors (yeast, Escherichia coli , Bacillus subtilis , Agrobacterium rhizogenes 532 and Agrobacterium tumefaciens C 58) were more effective in eliciting the response when compared to the abiotic elicitors (CdCl 2 , AgNO 3 , CuCl 2 and HgCl 2 ). Yeast has shown to stimulate maximum accumulation of 13.5 mg/g DCW andrographolide, which was found to be 8.82-fold higher than the untreated cultures.